Flexible organic optoelectronic devices: Design, fabrication, and applications - Yuanhe Wang; Yanlong Wen; Xiaoxiao Zhuang; Shihao Liu; Letian Zhang; Wenfa Xie (APL Photonics, 2024)
Flexible organic optoelectronic devices (FOODs) are rapidly emerging as a transformative technology in consumer electronics due to their exceptional bendability, lightweight, and seamless integration capabilities. This review provides a comprehensive overview of FOODs, including flexible organic light-emitting devices, organic photodetectors, and organic solar cells. We delve into their structural design, fundamental operating principles, and the unique advantages and challenges they present for applications requiring flexibility. Following this, the review explores the critical components of FOODs, with a particular focus on transparent conductive electrodes (TCEs) and innovative substrate materials. We discuss various TCE types, including carbon-based, metal network, and composite designs. Additionally, we explore the use of novel substrates like fibers, fabrics, and paper. Finally, the review examines current fabrication and encapsulation techniques employed for these flexible devices. We conclude by highlighting promising applications of FOODs in diverse fields, including biomedical science and intelligent interactive technologies.